2016
DOI: 10.1161/circresaha.115.308178
|View full text |Cite
|
Sign up to set email alerts
|

Protective Roles of Endothelial AMP-Activated Protein Kinase Against Hypoxia-Induced Pulmonary Hypertension in Mice

Abstract: C ytokines/chemokines and growth factors regulate pulmonary endothelial function and influence the development of pulmonary arterial hypertension (PAH).1 PAH is characterized by pulmonary vascular remodeling and perivascular inflammation, leading to right ventricular (RV) failure and premature death. [2][3][4][5] Endothelial dysfunction is a crucial pathogenic status that triggers a variety of vascular disorders, such as PAH. 6,7 Endothelial dysfunction is also considered a key underlying feature in most forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
108
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(112 citation statements)
references
References 57 publications
4
108
0
Order By: Relevance
“…Indeed, AMPK activation by oral administration of metformin has been shown to inhibit pulmonary VSMC proliferation and ameliorate the development of pulmonary hypertension. 1 The pathobiology of cardiovascular diseases includes endothelial dysfunction, Figure. Roles of AMP-activated protein kinase (AMPK)-α1 and AMPK-α2 in endothelial cells, vascular smooth muscle cells (VSMCs), and inflammatory cells. The RhoA (Ras homolog gene family member A)/Rho-kinase system is activated by many mechanisms, including signals from cytokines/chemokines and growth factors, leading to agonist-induced VSMC contraction.…”
Section: Clinical Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, AMPK activation by oral administration of metformin has been shown to inhibit pulmonary VSMC proliferation and ameliorate the development of pulmonary hypertension. 1 The pathobiology of cardiovascular diseases includes endothelial dysfunction, Figure. Roles of AMP-activated protein kinase (AMPK)-α1 and AMPK-α2 in endothelial cells, vascular smooth muscle cells (VSMCs), and inflammatory cells. The RhoA (Ras homolog gene family member A)/Rho-kinase system is activated by many mechanisms, including signals from cytokines/chemokines and growth factors, leading to agonist-induced VSMC contraction.…”
Section: Clinical Significancementioning
confidence: 99%
“…irculating cytokines/chemokines and growth factors regulate endothelial function 1 and influence the development of cardiovascular diseases. 2 Cardiovascular diseases are characterized by endothelial dysfunction, 3 vascular smooth muscle cell (VSMC) proliferation, 4 and inflammatory cell migration, leading to obliteration or excessive enlargement of vascular lumens.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary artery ECs are important for pulmonary vascular homeostasis whereas EC dysfunction accelerates the development of PH. 15,43, 46 As a degree research project, I demonstrated the protective roles of the endogenous erythropoietin (Epo)/Epo receptor (EpoR) system in endothelial function and homeostasis. 21 Additionally, EpoR −/− -rescued mice revealed a crucial role of the endogenous Epo/EpoR system in the ischemic heart 22 and ischemia-induced angiogenesis.…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%
“…59-61 imaging techniques to evaluate pulmonary arterial remodeling in patients with PAH have been developed, 62, 63 and, in addition, it has been found that pravastatin and metformin ameliorate hypoxia-induced PH in mice. 25, 46 Recently, microarray analyses using PAHPASMCs to identify further common pathogenic proteins showed significant changes in 1,858 genes in PAH-PASMCs compared with control PASMCs. Some novel targets to develop therapeutic agents for patients with PAH were identified (Figure 2).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%